Ubodzy w przepowiadaniu proroka Amosa (Am 2, 6b-7a; 4, 1b; 5, 11a; 12b i 8, 4. 6) - Szwarc, Urszula (The Biblical Annals, 2017)
The article deals with the teaching about the poor in the Book of Amos. The first part is a detailed analysis of Am. 2, 6b-7a; 4, 1b; 5, 11a. 12b; 8, 4. 6, concentrating on the Hagiographer’s terminology. The second part comprises more general conclusions. Our study leads to the conclusion that terms saddîq, ʽebjôn/ ʽebjônîm, dal/dallîm, ʽănawîm, ʽanwê- ʼareṣ, which denote the poor, are synonyms. Hence, the title saddîq is to be referred to poor, the ignored, the oppressed rather than solely to the rich and prominent as has traditionally been done. Furthermore, Amos stresses the personal dignity of those generally held in contempt and belonging to the lowest social strata. In expressing these truths, the Book of Amos is independent of the teachings of the wisdom writers.